Bile cast syndrome: Diagnosis and management, a case series - Mir, Fahad F.; Jonnalagadda, Sreenivasa S. (Endoscopy International Open, 2017)
Background and study aims Bile cast syndrome (BCS) is a complication of orthotopic liver transplantation (OLT). It occurs in 4 % to 18 % of OLT recipients and can present as cholangitis and graft damage or loss. Twenty-two percent of patients with BCS require repeat OLT. The diagnosis and management of BCS can be challenging. Our aim is to share our experience with BCS and to briefly review the diagnosis and management of the condition.